THE INFLUENCE OF INDEPENDENCE, PROFESSIONAL SKEPTISM AND PROFESSIONAL ETHICS ON AUDITOR PERFORMANCE (Empirical Study at a Public Accounting Firm in South Jakarta) - Melisa Nurbeti; Arni Karina; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
The aim of this research is to determine the influence of independence, professional skepticism and professional ethics on the performance of auditors at Public Accounting Firms in the South Jakarta Region. The analytical method in this research uses the convenience sampling method. The data obtained was primary data by distributing questionnaires. The data analysis method used is statistical analysis in the form of multiple linear regression tests. Data was processed using SPSS version 26.0. Respondents in this study are auditors who work at Public Accounting Firms (KAP) which are registered in the directory of Public Accounting Firms in the South Jakarta area based on records of the Indonesian Institute of Public Accountants (IAPI), the sample in this study was 124 respondents. The analytical method in this research uses the convenience sampling method. The data obtained was primary data by distributing questionnaires. The data analysis method used is statistical analysis in the form of multiple linear regression tests. Data was processed using SPSS version 26.0. The results of this research show that independence, professional skepticism and professional ethics influence auditor performance. The results of the partial test (t-test) show that all have a significant positive effect on auditor performance. Based on the results of the multiple linear regression test, it was found that the most dominant variable was the professional ethics variable.